Understanding livelihood changes in the charcoal and baobab value chains during Covid-19 in rural Mozambique: The role of power, risk and civic-based stakeholder conventions. Issue 140 (March 2023) - Krauss, Judith E.; Castro, Eduardo; Kingman, Andrew; Nuvunga, Milagre; Ryan, Casey
Abstract: Non-pharmaceutical interventions (NPIs) to reduce the transmission of Covid-19 had different repercussions for domestic, regional and global value chains, but empirical data are sparse on specific dynamics, particularly on their implications for value-chain stakeholders' local livelihoods. Through research including weekly phone interviews (n = 273 from May to July 2020) with panellists in six Mozambican communities, our research traced firstly how the baobab and charcoal value chains were affected by Covid NPIs, particularly in terms of producers' livelihoods. Secondly, we ask how our findings advance our understanding of the role of civic-based stakeholder conventions and different types of power in building viable local livelihoods. Our conceptual lens is based on a synthesis of value-chain and production-network analysis, convention theory and livelihood resilience focusing on power and risk. We found that Covid trading and transport restrictions considerably re-shaped value chains, albeit in different ways in each value chain. The global baobab value chain continued to provide earnings particularly to women, when other income sources were eliminated, with socially oriented stakeholders altering their operations to accommodate pandemic restrictions. By contrast, producers involved in the domestic, solely market-oriented charcoal value chain saw their selling opportunities and incomes reduced, with hunger rising in charcoal-dependent communities. Our paper argues that local livelihoods were more resilient under Covid NPIs if civic-based conventions and collective, social power were present.